2019
DOI: 10.14710/jtsiskom.7.3.2019.103-108
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Menggunakan Algoritma Apriori untuk Rekomendasi Produk bagi Pelanggan

Abstract: The implementation of a marketing strategy requires a reference so that promotion can be on target, such as by looking for similarities between product items. This study examines the application of the association rule method and apriori algorithm to the purchase transaction dataset to assist in forming candidate combinations among product items for customer recommended product promotion. The purchase transaction dataset was collected in October and November 2018 with a total data of 1027. In the experiment, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
46

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 4 publications
0
9
0
46
Order By: Relevance
“…Minimum support 50% produces 12 frequent itemsets with itemset of 3. In Table 3, it can be concluded that the greater the minimum support, the fewer the number of items produced [2][7] and the stronger the association relationship between attributes in the rules formed [20]. Table 4, with a minimum support of 10%, it can see the itemsets formed and the items, for ex sample the itemset of four consists of classes or brands PYO, BON, Q BY and YSL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimum support 50% produces 12 frequent itemsets with itemset of 3. In Table 3, it can be concluded that the greater the minimum support, the fewer the number of items produced [2][7] and the stronger the association relationship between attributes in the rules formed [20]. Table 4, with a minimum support of 10%, it can see the itemsets formed and the items, for ex sample the itemset of four consists of classes or brands PYO, BON, Q BY and YSL.…”
Section: Discussionmentioning
confidence: 99%
“…Benchmark Confidence = [20] Information: Nc = number of transactions with items that become consequent.…”
Section: Analysis Of the Effects Of Minimum Support And Minimum Confimentioning
confidence: 99%
“…Association Rule direkomendasi dalam memudahkan pemetaan dalam penyediaan produk pertanian bagi petani dalam penyediaan dan pemasaran hasil pertanian yang menjadi pavorit masyarakat berdasarkan itemset transaksi yang perna dilakukan sebagai rekomendasi bagi petani [7]. C. Algoritma Apriori Algoritma Apriori dengan asosiasi yang digunakan sebagai rekomendasi bagi produsen dalam pengambilan keputusan dalam promosi produk untuk kebutuhan konsumen berdasarkan nilai support dan confidence minimum agar tepat sasaran berdasarkan kesamaan di setiap item produk [8]. Salah satu cara kerja dari Algoritma Apriori adalah dengan frequent itemset sebagai pencarian dalam teknik rule association karena menggunakan basis pengetahuan untuk mengukur frekuensi kemunculan data yang sama dikenal dengan istilah frekuent itemset [9].…”
Section: B Assocition Ruleunclassified
“…Selain itu apriori juga dapat digunakan untuk mendapatkan pola pembelian konsumen terhadap suatu produk, hal ini berguna untuk menentukan keterkaitan antar produk yang dibeli [5]. Penelitian ini menggunakan algoritma apriori karena kesederhanaan dan kemudahan algoritma ini dalam menangani data yang besar namun memiliki keterbatasan dalam pengolahan datanya [6].…”
Section: Abstactunclassified